Analisis Hubungan Faktor Sosial Ekonomi dan Sebaran Tindak Kriminalitas di Jawa Barat Tahun 2024 dengan Pendekatan Statistika Spasial - Hermawanti, Lisma; Dewi Kania Sari (Jurnal Serambi Engineering, 2025)
West Java Province has a population of more than 50 million people with complex socio-economic dynamics. Factors such as population density, poverty rate, open unemployment, and the Human Development Index (HDI) are suspected to influence the level of crime. According to the National Crime Information Center (2024), there were 43,616 criminal cases in West Java with a crime rate of 86.63 per 100,000 population. This study aims to analyze the relationship between socio-economic factors and crime distribution in West Java in 2024 using a spatial statistics approach, namely Global Moran’s I, Local Indicator of Spatial Association (LISA), and Ordinary Least Squares (OLS) regression. The results show that crime distribution tends to be random, with weak clusters in urban areas. The OLS analysis reveals that among the four independent variables, only HDI has a positive and significant effect on crime, while population density, poverty, and open unemployment are not significant. These findings indicate that higher human development is not always associated with a reduction in crime, particularly in urban areas with intensive socio-economic activities.